Strain-controlled iso-thermal fatigue behavior of Co–29Cr–6Mo used for tooling materials in Al die casting - Tunthawiroon, Phacharaphon; Li, Yunping; Koizumi, Yuichiro; Chiba, Akihiko (Materials Science and Engineering: A, 2017)
Iso–thermal (IF) fatigue behavior of a singleε-phase Co–Cr–Mo alloy used as Al die casting mold is investigated in details at temperatures of 400, 500, 600, and 700°C and applied mechanical strains of 0.1%, 0.2%, 0.3% and 0.4%. The results indicate that for a given applied mechanical strain, higher temperature promotes the occurrence of oxidation on alloy surface, resulting in a shorter fatigue life compared to the tests at lower temperature; at a given temperature, larger applied strain amplitude gives rise to shorter fatigue life. Microstructural observation indicates that grain boundary oxidation plays a significant role for crack nucleation at high temperature. The cracks are found to initiate intergranularly and propagate in a mixed intergranular and transgranular mode.